Hormonal Receptors in Skeletal Muscles of Dystrophic Mdx Mice. (27th December 2012) - Feder, David; Rodrigues Barros Godoy, Ivan; Guimarães Pereira, Maira Lazzarini; Silva, Cledson Silveira; Nogueira Silvestre, Diego; Fonseca, Fernando Luiz Affonso; Alves de Siqueira Carvalho, Alzira; Aparecida dos Santos, Rosangela; Catteli Carvalho, Maria Helena
Abstract : Introduction . Several evidences show that muscles have an endocrine function. Glucocorticoid, estrogen, progesterone, and testosterone receptors have already been found in normal skeletal muscles, but not in dystrophic muscles. Methods . The gene expression of hormone receptors was compared between dystrophic and healthy muscles in mdx and C57BL6 mice strains. Results . The mdx mice showed a significant increase in the steroid receptors mRNA when compared to the C57BL6 mice: levels of androgen(s) receptors in the heart, estrogen receptors alpha in the EDL, and estrogen receptors beta in the quadriceps were increased. In addition, significant lowered levels of some other hormone receptors were found: corticosteroid receptors in the EDL and estrogen receptors alpha in the quadriceps. Conclusion . Dystrophic muscles bear significant differences in the expression of hormone receptors when compared to the C57BL6 mice strain. The importance of such differences is yet to be better understood.